Prisoners of Myth : The Leadership of the Tennessee Valley Authority, 1933-1990 - Hargrove, Erwin C. (Book collections on Project MUSE., 2001)
Prisoners of Myth is the first comprehensive history of the Tennessee Valley Authority from its creation to the present day. It is also a telling case study of organizational evolution and decline. Building on Philip Selznick's classic work TVA and the Grass Roots (1949), a seminal text in the theoretical study of bureaucracy, Erwin Hargrove analyzes the organizational culture of the TVA by looking at the actions of its leaders over six decades--from the heroic years of the New Deal and World War II through the postwar period of consolidation and growth to the time of troubles from 1970 onward.